2003
DOI: 10.1038/sj.thj.6200249
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic concordance of two portable monitors and two routine automatic oral anticoagulant monitoring systems using as reference the manual prothrombin time technique

Abstract: Two models of capillary blood prothrombin time (PT) monitoring systems were evaluated for analytical performance and then compared with two routine PT systems using the reference manual technique and a high-sensitivity thromboplastin. Two sets of 60 and 80 plasmas were analyzed from anticoagulated patients stabilized over 3 months in an INR range 2-3.5 for therapy. Capillary PT determination was performed in two portable monitors, CoaguChek S and CoaguChek PT (Roche Diagnostics), and plasma automatic methods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Such monitors need to be accurate over the full therapeutic range of the INR, between 2·0–4·5, and require an acceptable independent evaluation (Fitzmaurice & Machin, 2001). A number of studies have proved comparability between POC testing and conventional laboratory techniques based on POC testing by healthcare professionals (Bachour et al , 2001; Vacas et al , 2001; Havrda et al , 2002; Shiach et al , 2002; Loebstein et al , 2003; Jackson et al , 2004), whereas others have questioned the reliability of POC test INR results (Poller et al , 2003; Vacas et al , 2003). Of note, INR results obtained by technically skilled healthcare professionals using POC testing devices have been reported to be more reliable than those achieved by non‐technical trained individuals (Delaney et al , 1999).…”
mentioning
confidence: 99%
“…Such monitors need to be accurate over the full therapeutic range of the INR, between 2·0–4·5, and require an acceptable independent evaluation (Fitzmaurice & Machin, 2001). A number of studies have proved comparability between POC testing and conventional laboratory techniques based on POC testing by healthcare professionals (Bachour et al , 2001; Vacas et al , 2001; Havrda et al , 2002; Shiach et al , 2002; Loebstein et al , 2003; Jackson et al , 2004), whereas others have questioned the reliability of POC test INR results (Poller et al , 2003; Vacas et al , 2003). Of note, INR results obtained by technically skilled healthcare professionals using POC testing devices have been reported to be more reliable than those achieved by non‐technical trained individuals (Delaney et al , 1999).…”
mentioning
confidence: 99%
“…Several studies indicated an excellent correlation between photo‐optical and electromechanical coagulation analysers, while the comparison between POC and laboratory or manual INRs showed a certain variability in the results, with potential clinical disagreement and differences in VKA dosing . However, it is not known which test actually correlates better with the overall blood coagulation potential, because these three INR methods have never been compared simultaneously with global coagulation assays.…”
Section: Introductionmentioning
confidence: 99%